2021
DOI: 10.1021/acs.orglett.1c03234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Study of Heteropolycyclic and Carbazole Motif: Nickel-Catalyzed Chelate-Assisted Cascade C–H Activations/Annulations

Abstract: Herein, nickel-catalyzed synthesis of polyarylcarbazole through sequential C–H bond activations has been described. Regioselective indole C2/C3 functionalization has been achieved in the presence of indole C7-H, which is quite challenging. In addition, this approach also gives easy access to building a heteropolycyclic motif through C6/C7 C–H functionalization of indoline. This methodology is not limited to aromatic internal alkynes as coupling partners; aliphatic alkynes have also shown good tolerance. Notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Recently, the Kim and Ravikumar groups developed an ‘N’-directed similar kind of homologation of hetero(arenes) under Cp*Rh( iii ) [ 126 → 127 ] and Ni( ii ) [ 128 → 129 and 130 ] catalysts (Scheme 33E-F). 76…”
Section: Ortho-selective Double Annulation Of Two Different C–h Bondsmentioning
confidence: 99%
“…Recently, the Kim and Ravikumar groups developed an ‘N’-directed similar kind of homologation of hetero(arenes) under Cp*Rh( iii ) [ 126 → 127 ] and Ni( ii ) [ 128 → 129 and 130 ] catalysts (Scheme 33E-F). 76…”
Section: Ortho-selective Double Annulation Of Two Different C–h Bondsmentioning
confidence: 99%
“…Furthermore, in 2021 Ravikumar et al demonstrated the synthesis of poly-heterocyclic indoline 184 and bioactive carbazole motifs 186 via sequential C–H bond activation of indoline 183 and indole 185 using alkynes 182 (Scheme 61). 72 This selective functionalisation of indole, even in the presence of C7–H, makes this approach unique. The reaction conditions were optimized, following which the scope of the reaction was examined.…”
Section: Various Transition Metal-catalysed Unusual Reactions Of Alkynesmentioning
confidence: 99%
“…An unwanted [2+2+2] cycloaddition reaction was observed for alkylsubstituted ynamides, thus giving lower yields. 71 This selective functionalization of indole, even in the presence of C7-H, makes this approach unique. The reaction condition was optimized, following which the scope of the reaction was examined.…”
Section: Scheme 58a Cobalt Catalyzed Regioselective C(4)-h Functional...mentioning
confidence: 99%